PRIMIPARA POST PARTUM DEPRESSION DIAGNOSIS AND TREATMENT - Esha Pradnyana; Wayan Westa; Nyoman Ratep (E-Jurnal Medika Udayana, 2013)
Pregnancy and the first child birth is an influential complex event for a mother, which is where everything including phsycal and psyological aspects. This change can make mother psyological disorder, that can lead into depression after childbearing that call post childbearing depression or post partum depression. A wide review at 59 study make a result that 13% among primipara can suffer post partum depression 12 weeks after childbearing. Estabilishmet of this diagnosis, besides from history and symptoms, and can be supported through test Edinburgh Postnatal Depression Scale( EPDS ). Patient with post partum depression, given treatment with antidepressant drug. Breastfeeding is not only to reduce stress for the mother, but also reduce the level of stress on a baby when his mother suffered depression